Striatal reward sensitivity predicts therapy-related neural changes in alcohol addiction - Becker, Alena; Gerchen, Martin Fungisai; Kirsch, Martina; Hoffmann, Sabine; Kiefer, Falk; Kirsch, Peter (European archives of psychiatry and clinical neuroscience, 2018)
Individual differences in reward sensitivity along with weakened executive control are characteristic for alcohol use disorder (AUD). Emerging translational models of psychotherapy propose the integration of such neurobiological risk profiles to elucidate the mechanisms underlying behavior change in order to improve intervention efficacy. The primary aim of the study was to investigate whether striatal baseline reward sensitivity can be used as a neurobiological predictor of intervention-specific changes in neural functioning during AUD therapy. Fifty-eight detoxified AUD patients were randomly assigned to either receive cue exposure training (CET + TAU, N = 40) or treatment as usual (TAU only, N = 18). Pre- and post-treatment sensitivity to reward was assessed by a functional magnetic resonance imaging monetary reward paradigm. A moderated multiple regression analysis revealed a positive relationship between striatal baseline reward sensitivity and activation changes in the superior frontal gyrus and anterior cingulate cortex (ACC) after CET + TAU in contrast to a negative relationship after TAU only. Over all subjects, a stronger signal change in the superior frontal gyrus and ACC was associated with increased self-efficacy to abstain alcohol. These results provide evidence that reward sensitivity at baseline predicts neural changes in inhibitory networks after receiving CET + TAU. Striatal reward sensitivity might be a promising neurobiological marker to inform therapeutic decisions.